Enhancing Integration between Physicians and Nurses to Improve the Quality of Health Care: A Review of the Clinical Work Environment - Alharbi, Nawaf Mutiq Owaytiq; Almalki, Hanan Hameed; Alsiyami, Dhuha Abdullah; Barnawi, Ajlal Ali; Hakami, Amjad Mohammed Ali; Alshanqiti, Doaa Abduallah Mahmoud; Ibrahim, Nada Kamil Abdullah; Masmali, Neamah Essa Ahmed (Journal of Posthumanism, 2024)
This review examines the impact of physician-nurse integration on healthcare quality, highlighting its importance in modern health systems. It analyzes peer-reviewed literature and reports from leading organizations like the Institute of Medicine and WHO. Key findings show that effective integration leads to improved patient safety, clinical outcomes, patient experience, operational efficiency, and provider well-being. However, barriers like professional hierarchies, communication failures, and unsupportive organizational cultures hinder collaboration. To overcome these, a multi-pronged strategy is suggested, including changes in education through Interprofessional Education (IPE), adoption of clinical practice innovations, supportive leadership, and strategic use of enabling technologies. The review concludes that enhancing physician-nurse integration is a fundamental requirement for delivering safe, effective, and patient-centered care in the 21st century. The findings have significant implications for clinical practice, healthcare policy, and future research, emphasizing the need for a systemic shift towards a fully integrated clinical workforce.